2021
DOI: 10.3390/ani11061584
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Behaviour in Italian Mediterranean Buffaloes

Abstract: The aim of this study was to describe the neonatal and maternal behaviour of Italian Mediterranean buffaloes. Thirty primiparous buffaloes were moved into individual pens 12.5 (±2.5) days before calving. Maternal and neonatal behaviours were recorded for 48 h after calving and the analysis was performed in continuous sampling with the software BORIS. Calves’ clinical evaluations (temperature, weight, and heart and respiratory rates) were performed at different time intervals and correlated with behavioural dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…All data were normally distributed. Mean time between birth and calves first suckle was 212 ± 110 min, as reported by Lanzoni et al (2020) [42]. The mean IgG content measured by ELISA in first-milking maternal colostrum was 64.9 ± 29.3 mg/mL with a range from 21.0 to 110.0 mg/mL.…”
Section: Descriptive Statistics: Brix and Elisa Measurementssupporting
confidence: 72%
“…All data were normally distributed. Mean time between birth and calves first suckle was 212 ± 110 min, as reported by Lanzoni et al (2020) [42]. The mean IgG content measured by ELISA in first-milking maternal colostrum was 64.9 ± 29.3 mg/mL with a range from 21.0 to 110.0 mg/mL.…”
Section: Descriptive Statistics: Brix and Elisa Measurementssupporting
confidence: 72%
“…In general, the offspring stand and suckle shortly after birth [26]. Lanzoni et al [22] found that Italian Mediterranean buffalo calves took on average 212.0 ± 110.0 min to suckle, and this behavior was mainly shown during the first six hours. Furthermore, they also found that calves that took more time to stand also took more time to make the first suckling attempt, results that could be related to the calf's vitality.…”
Section: Strategies Of Maternal Carementioning
confidence: 99%
“…Multiparous mothers spent more time licking their calves than primiparous, which suggests a higher degree of maternal care expressed by more experienced mothers [58]. In Italian Mediterranean buffalo the dams mainly groomed the calf during the first six hours after calving, to ensure the formation of the cow-calf bond; thereafter, the behavior decreased over time [22]. Both in cattle and buffalo, cows ingest the fetal membranes during this process of conditioning and cleaning of the offspring, whereas sheep and goats normally do not express this behavior [24,26].…”
Section: Tactile Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Water buffalo ( Bubalus bubalis ) is a valuable species with excellent zootechnical characteristics for both milk and meat production [ 1 ]. As a result of the growing economic interest, buffalo farming moved from traditional extensive techniques to more intensive systems [ 2 , 3 ]. Such changes increased the expression of undesired behaviours, such as excessive aggressive interactions, negatively affecting buffalo behaviour, welfare and production efficiency [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%